Pengambilan Keputusan Sistem Penjaminan Mutu Perguruan Tinggi menggunakan MOORA, SAW, WP, dan WSM - Sunardi; Abdul Fadlil; Ryan Fitrian Pahlevi (Ikatan Ahli Informatika Indonesia (IAII), 2021)
Higher Education Quality Assurance (QA) is regulated in Quality Standards and the number of criteria as well as its relationship with the implementation of the Quality Assurance System (QAS), namely the Internal and External Quality Assurance System (IHSG). . The research is focused on analyzing 4 decision-making methods or Decision Support Systems (DSS) for QAS in MAC. The purpose of this study is to classify standard data and MAC criteria in business processes into a database that is integrated with the QAS decision-making method. The analysis was carried out on 4 multi-criteria decision-making methods that will be used in the QAS-MAC decision-making process, namely: Moora, SAW, WP, and WSM. These methods were tested on a quality standard database and then assessed by comparison, namely relevance, features, accuracy, precision, reliability, effectiveness, efficiency, strengths, and weaknesses. Decision Making Methods as a determinant of Business Process priorities become information for PTMA Leaders in predicting strategic activities. The value of the method analysis shows that 4 decision-making methods are Moora (75%), SAW (75%), WP (94%), and WSM (94%).